Analisis Rasio Likuiditas dan Rasio Profitabilitas Pada PT. Bank Mandiri (persero) tbk Periode 2016-2019 - Nelly; Zein Ghozali; Masnoni; Sri Sutandi; Roy Saleh (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The purpose of research for writing this thesis is to find out the analysis of financial statements at PT. Bank Mandiri (Persero) Tbk in 2016-2019. Based on the description above, the author compiled this thesis with the title